A study of fetomaternal outcome in induction of labour in third trimester oligohydramnios - Sharma, Nalini; Gehlot, Hanslata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The Induction of labor in oligohydramnios poses a dilemma for obstetrician. Studies are limited with variable results. This study aims at finding whether isolated oligohydramnios is an indication for operative delivery or labor induction followed by vaginal delivery is possible. Methods: A prospective study carried out on females delivered in study duration in Umaid Hospital, Jodhpur, Rajasthan. Outcomes studied were gestational age at delivery, colour of amniotic fluid, FHR tracings, mode of delivery, indication for cesarean section or instrumental delivery, Apgar score at one minute and five minutes, birth weight, admission to Neonatal Intensive Care Unit (NICU), perinatal morbidity and perinatal mortality. Descriptive statistics were applied and data was represented on frequency tables, graphs and diagrams. Results: 40% of subjects had amniotic fluid index (AFI) <5 cm and 60% demonstrated AFI between 5-7 cm. 60% of patients induced delivered vaginally with (38.33%) having AFI <5 cm. Operative delivery was resorted to in 40% of patients. Perinatal outcomes resulted in total 97% of babies discharged in healthy condition. Conclusions: Labor induction is feasible in idiopathic oligohydramnios. Fetal distress is the most feared and predicted outcome with labor induction in oligohydramnios. This study deduced that in majority- reason for c-sections was failed labor induction due the poor Bishop's score, not fetal reasons. We hope by putting at rest apprehensions of obstetrician regarding this notion rate of c-sections could be reduced.